Pelatihan Inovasi Pembuatan Kue Tradisional Berbahan Dasar Singkong Bagi Ibu Rumah Tangga Sebagai Upaya Meningkatkan Penghasilan Keluarga - Artanti, Guspri Devi; Mariani, Mariani (Universitas Nusantara PGRI Kediri, 2022)
Benda Baru Village, located in Pamulang sub-district, South Tangerang, has the potential for local food ingredients in the form of cassava which is generally processed simply for own consumption or sold as a home-based business. This simple processing causes the value and selling price of the product to be low. This community service activity aims to improve the ability of the Benda Baru village community in processing cassava and innovate traditional cake making that can increase the selling value of processed cassava products as an effort to improve family welfare. This activity was attended by 19 participants who are housewives in the Benda Baru sub-district which were carried out online using lectures, demonstrations, and evaluation methods. Evaluation of activities is carried out by filling out a pre-test and post-test by participants which is then calculated by using a gain test, as well as filling out a questionnaire on the satisfaction of the activity implementation. Gain-score results obtained a value of 0.8 which means that there is an high increase in the knowledge of participants. The results of the questionnaire stated that community service activity went well, the material was conveyed clearly, and sparked the interest of the training participants to try to practice the cake that was demonstrated. Based on the results of the gain test and filling out the questionnaire, it can be concluded that this community service activity went well, had a positive impact on the training participants, became an inspiration for fulfilling family snacks, and was used as a business opportunity to help improve the family economy.